2020
DOI: 10.3390/ijerph17072612
|View full text |Cite
|
Sign up to set email alerts
|

Infant Cranial Deformity: Cranial Helmet Therapy or Physiotherapy?

Abstract: Objective: To compare cranial helmet therapy (CHT) and physiotherapy (PT) for the effective treatment of positional plagiocephaly in infants in terms of improving functional recovery. Methods: This was a prospective cohort study involving 48 infants between 5–10 months of age with cranial deformities. The Cranial Vault Asymmetry Index (CVAI) and the Brunet–Lezine scale were calculated at the initiation of the study and after 40 treatment sessions. Results: The infants’ first assessment showed a delay in overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Our study further supports the effectiveness of helmet therapy, assuming good protocol compliance. Recent studies showed no statistically significant difference between helmet therapy and physiotherapy, but the authors advised the use of a combination of both techniques, depending on various factors [31]. However, there was no control group in this study to confirm that the improvement was the result of helmet therapy alone, without any counter-positioning or physiotherapy.…”
Section: Discussionmentioning
confidence: 60%
“…Our study further supports the effectiveness of helmet therapy, assuming good protocol compliance. Recent studies showed no statistically significant difference between helmet therapy and physiotherapy, but the authors advised the use of a combination of both techniques, depending on various factors [31]. However, there was no control group in this study to confirm that the improvement was the result of helmet therapy alone, without any counter-positioning or physiotherapy.…”
Section: Discussionmentioning
confidence: 60%
“…Inclusion criteria for the study were as follows: (1) brain CT performed for suspected head trauma and diagnosed normal and (2) age ≤7 years. The exclusion criteria were as follows: (1)…”
Section: Patientsmentioning
confidence: 99%
“…Depending on the skull shape, cranial deformities can be divided into plagiocephaly, dolichocephaly, and brachycephaly [1]. Plagiocephaly is correctly applied to describe only flattening on one side of the head.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak can be observed at four months, and percentages are low after 8 months. Many cases of PP improve over time, but scientific evidence suggests that conservative management strategies can safely and effectively minimize the degree of cranial asymmetry [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%